Adaptation and validation of moral distress thermometer in Chinese nurses - Xu Tian; Xiuni Gan; Yi Ren; Feili Li; Maria F. Jimenez Herrera; Fangrong Liu (BMC, 2024)
Abstract Background Moral distress seriously affects professional nurses, and a number of instruments have been developed to measure the level of moral distress. The moral distress thermometer (MDT) is one of the commonly used instruments that can rapidly measure real-time moral distress; however, it remains unclear whether it is still useful in the Chinese cultural context. Aim This study aimed to adapt and validate the MDT among Chinese registered nurses. Research design An online, cross-sectional, survey study of adapting and validating Chinese version of MDT. Participants and research context A total of 182 registered nurses effectively finished this survey. The correlation between MDT score and the score of the moral distress scale-revised version (MDS-R) was used for evaluating convergent validity, and MDT scores of registered nurses who working in different departments and who made different actions to the final question of the MDS-R were compared by using one-way ANOVA to evaluate construct validity. Ethical considerations The Ethics Committee of Chongqing Traditional Chinese Medicine Hospital approved this study. Results The Chinese version of MDT was described as relevant to measure moral distress, with a reported item-level content validity index (I-CVI) and scale-level CVI (S-CVI) of 1. The mean MDT score and mean MDS-R score were 2.54 and 38.66, respectively, and the correlation between these two scores was significantly moderate (r = 0.41). Nurses working different departments reported different levels of moral distress, and those working in intensive care unit reported the highest level of moral distress than those working in other departments (p = 0.04). The MDT scores between nurses who presented different actions to their position were also significantly different, and those who had ever left and those who had considered leaving but did not leave reported significantly higher moral distress. Conclusion The MDT is a reliable, valid, and easy-to-use instrument to rapidly measure the real-time moral distress of registered nurses in China.